Prospective, open‐label, rater‐blinded and self‐controlled pilot study of the treatment of proliferating superficial infantile hemangiomas with 0.5% topical timolol cream versus 595‐nm pulsed dye laser. Issue 6 (13th February 2017) - Ying, Hanru; Zou, Yun; Yu, Wenxin; Qiu, Yajing; Ma, Gang; Chang, Lei; Gu, Yifei; Lyu, Dongze; Lin, Xiaoxi
Abstract: Topical timolol and 595‐nm pulsed dye laser (PDL) are both widely used in the treatment of superficial infantile hemangiomas (IH). However, to date, there is no reliable study comparing the therapeutic outcomes between the two treatment options. We designed the present study to evaluate and compare the efficacy and safety of timolol cream and PDL in the treatment of superficial proliferating IH. Twenty‐one patients with superficial IH were included in the study. Each lesion was divided into two regions; one part was treated with 0.5% topical timolol cream four times daily, and the other part was treated monthly with PDL. Both treatments were continued for 2–6 months. Five independent and blinded assessors were asked to judge the results in both the topical timolol‐treated and PDL‐treated parts by comparing photographs taken before and after treatment. Both treatments resulted in significant clinical improvements after 3.39 sessions in the 2‐month follow up. The average visual evaluation showed that PDL had significantly better results than topical timolol (6.55 ± 2.26 to 4.98 ± 2.92, P < 0.01). No patients experienced permanent side‐effects during the treatment. Our short‐term study revealed that PDL had better results compared with topical timolol cream application in the treatment of superficial proliferating IH. Further studies with longer follow‐up time and larger sample size are required to validate our findings.